The West Bank Wall. Issue 3 (2nd July 2016) - Jones, Reece; Leuenberger, Christine; Wills, Emily Regan
ABSTRACT: This introduction to the special issue sets out to bring some clarity and organization to the diverse bodies of literature on the construction, lived experience, and consequences of the West Bank Wall. We review the literature on the Wall and identify three broad themes: the significance of the Wall in the context of political negotiations, its disruption of daily life in the West Bank, and its role as a symbol in broader debates about sovereignty, territory, and the state in border studies.